The Impact of Social Support on Academic Resilience Mediated by Self-Regulated Learning - Runggu Nadeak; Nuraini MS; Amanah Surbakti (Journal of Educational, Health and Community Psychology, 2024)
High school students need resilience to cope with academic pressures and demands. This study aims to examine the mediating role of self-regulated learning on the effect of social support on academic resilience among high school students. For this purpose, the study population came from one of the high schools in Medan City with a total number of 615 students. This study used total sampling to obtain effective results and partial least square (PLS) SEM. SmartPLS 3.0 was used to analyse the data. The results of this study show that self-regulated learning is able to partially mediate between the influence of social support on students' academic resilience. In order to improve academic resilience, it is recommended that parents and teachers provide active support to students as a tangible manifestation of the social support provided to enhance the development of self-regulated learning in students